Value plurality and multifunctional commensuration in organisation: A systems-theoretical approach - Steffen Roth; Augusto Sales; Vladislav Valentinov (Systems Research and Behavioral Science, 2025)
This article aims to challenge the prevailing economic bias in studies of organised valuation and commensuration by exploring the broader plurality of values that organisations must manage. The article draws on social systems theory in the tradition of German sociologist Niklas Luhmann to conceptualise organisations as multifunctional systems of decisions that pertain to and commensurate a plurality values associated with a diverse set of value domains, also known as `function systems'. The utility of the proposed framework is demonstrated through cases related to carbon rationing and legal issues during the coronavirus crisis. A key finding is that commensuration is not limited to processes dominated by financial metrics, as political and educational metrics, among others, can also serve as primary drivers of commensuration processes, effectively guiding organisational decision-making. The paper demonstrates how organisations can effectively commensurate diverse value systems without relying solely on financial metrics and concludes that future research in non-/financial of valuation and commensuration will be crucial for developing more nuanced and multifaceted strategies and concepts, including multifunctional approaches to the formation, justification, and management of moral judgements and values.
Keywords: 300; carbon rationing; functional differentiation; non-economic quantification; non-financial valuation; social systems theory; sustainability